The complete mitochondrial genome of the Madagascar mother-of-pearl butterfly Salamis anteva (Insecta: Lepidoptera: Nymphalidae) - Melanie M. L. Lalonde; Jeffrey M. Marcus (Mitochondrial DNA. Part B. Resources, 2019)
The Madagascar mother-of-pearl (Salamis anteva) is a leaf-mimicking butterfly endemic to forests in southern Madagascar. Genome skimming by Illumina sequencing permitted assembly of a complete S. anteva circular mitogenome of 15,201 bp consisting of 80.6% AT nucleotides and with an arrangement of 22 tRNAs, 13 protein-coding genes, two rRNAs and a control region common to all butterflies. The mitogenome includes a COX1 gene with an atypical CGA start codon and four genes exhibiting incomplete stop codons. Phylogenetic reconstruction places S. antvea as sister to Yoma sabina within a monophyletic nymphalid tribe Junoniini. This is consistent with previous molecular phylogenetic hypotheses.